(untitled) (Faridpur Medical College Journal, 2013)
A prescription order is a written instruction of doctors to pharmacist to supply drugs in particular form to a patient and the directions to the patients regarding the use of medicines. This study was undertaken to observe the prescribing patterns of the private practitioners in Bangladesh, 430 prescriptions were collected randomly from Dhaka city and analyzed using WHO/INRUD indicators. There were average 3.40 drugs per prescription. Drugs were prescribed in generic name only in 0.20%. About 46.31% drugs were prescribed from the Essential Drug List, only 19% of prescriptions were complete in respect to patient medication information. Antibiotics were prescribed in 70.33% of the prescriptions; injections were prescribed in about 8.35% of the prescriptions. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13497 Faridpur Med. Coll. J. 2012;7(2): 51-53